2015
DOI: 10.1093/jjco/hyv139
|View full text |Cite
|
Sign up to set email alerts
|

Low-level Ki-67 expression as an independent predictor of bladder tumour recurrence in patients with primary upper tract urothelial carcinoma after radical nephroureterectomy

Abstract: Objective: To evaluate the association of molecular markers and conventional clinicopathological factors with bladder tumour recurrence in patients with primary upper tract urothelial carcinoma after radical nephroureterectomy. Methods: The expressions of Ki-67 and P53 were measured by immunohistochemical staining prospectively in 115 consecutive patients with primary upper tract urothelial carcinoma from March 2004 to February 2014. The Cox proportional hazards regression model was used to identify independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
(27 reference statements)
3
13
0
Order By: Relevance
“…Qamar et al found that higher p53 expression can be an indicator of tumor progression and early failure of local therapy, as well as early surgical intervention, especially for superficial carcinomas. Although, the opposite results were also described by some investigators [8][9]13].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Qamar et al found that higher p53 expression can be an indicator of tumor progression and early failure of local therapy, as well as early surgical intervention, especially for superficial carcinomas. Although, the opposite results were also described by some investigators [8][9]13].…”
Section: Discussionmentioning
confidence: 58%
“…P53 is a key tumor suppressor gene involved in genomic balance, genotoxic stress response, and cell cycle apoptosis stimulation. Some studies showed correlations in urothelial bladder cancer between p53 and tumor stage and grade [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In combination with CK20 overexpression, Ki-67 overexpression can serve as a predictor of pT1 urothelial bladder cancer recurrence [12]. Regarding UTUC, a previous study and this study show that low-level Ki-67 expression was an independent predictor of bladder tumor recurrence in patients without instillation therapy [13]. Our study also found that patients with low-level Ki-67 appeared to be more sensitive to intravesical chemotherapy; we also found that the subsequently recurring bladder tumors in patients with intravesical chemotherapy expressed more Ki-67 than those in the patients without intravesical chemotherapy.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to EGFR, Ki-67 overexpression is also suggestive of high tumor grade and poor prognosis [12,13]. In combination with CK20 overexpression, Ki-67 overexpression can serve as a predictor of pT1 urothelial bladder cancer recurrence [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation